Appraising Financial Development Indicators and Capital Market Performance : Empirical Evidence from Nigeria - Agbada, Andrew Omosioni (Finance & Economics Review, 2020)
This study appraised empirically Financial Development Indicators (FDIs) and Capital Market Performance in Nigeria. While Financial Depth, Financial Access and Financial Efficiency served as proxy for FDIs and independent variable; Market Capitalization was used as proxy for Capital Market Performance and the dependent variable. Primary data were sourced employing Survey design and analyzed using Pearson Product-Moment Correlation Coefficient, (PPMCC) technique denoted by ‘r’. The robustness of findings which showed that hypotheses one (H01) and two (H02) exhibited high coefficients and passed the test of significance led us to conclude that the variables: Financial Depth and Financial Access are relevant to policies formulated to affect Market Capitalization in Nigeria. However, hypothesis three (H03) portends rather low results suggesting that though a positive relationship exists between Financial Efficiency and Market Capitalization, the strength of relationship is moderate and cannot be considered too relevant to policies formulated to affect Market Capitalization in Nigeria. We therefore recommend that financial sector authorities and stakeholders should ensure that innovative facilities and policies that enable access to finance; that give ability to financial markets to imbibe large trade volumes be put instituted to facilitate proper development of the sector and that serious attention should be given to on-the-job-training, retraining and financial courses for employees to acquire industry knowledge of the job in order to enhance their performance.